What would happen if you wanted to find the derivative of the following function:

y^3 + y = 3x^2 - 5y^2

You would solve it the same way you normally solve for the dervative, but treating the y's differently. You would take the derivative the same way, but will multiply the derivative by dy/dx. Then, solve the equation for dy/dx. For instance, the derivative of y^3 is 3y^2 × dy/dx. So to find the derivative of the entire function:

y^3 + y = 3x^2 - 5y^2

(3y^2 × dy/dx) + (1 × dy/dx) = 6x - (10y × dy/dx)

6x = (3y^2 × dy/dx) + (1 × dy/dx) + (10y × dy/dx)

6x = dy/dx × (3y^2 + 10y + 1)

dy/dx = 6x ÷ (3y^2 + 10y + 1)

There is no current Design Scheme